THE SPIRITUAL-PHILOSOPHICAL ESSENCE OF PATRIOTISM AND THE SOCIAL-MORAL MATURITY OF THE INDIVIDUAL (Scientific journal of the Fergana State University, 2026)
This article examines the conceptual essence and social profile of a patriotic person in the context of modern societal development. The study analyzes key psychological, moral, and civic characteristics that shape patriotism as a personal and social value. The author explores the socio-cultural factors influencing the formation of patriotic identity and highlights the importance of patriotism in strengthening national cohesion, civic responsibility, and social stability. The article also discusses contemporary challenges to patriotic education and proposes theoretical approaches for fostering patriotically oriented individuals within society.